Quand le savant l’emporte sur le politique - David Diallo (Transatlantica)
In this article, I examine some of the reactions that William Julius Wilson’s The Declining Significance of Race has triggered among his colleagues and among black activists. I explain that some criticisms, clearly at odds with scientific research, are the result of ideological interpretations that completely divorce Wilson’s work from its scholarly context. Through my analysis of the controversy caused by Wilson thesis, I importantly address issues of methodology, analytical rigor, and objectivity in scholarly works and emphasize highly biased assumptions presented by myopic researchers who let racial and political ideology take precedence over objectivity.